Positive electrode active material and preparation method and application thereof
By introducing Na4Fex(PO4)2(P2O7) core and carbon cladding into sodium ferric pyrophosphate positive electrode material, combined with spray drying and fluidized drying treatment processes, the energy density and low-temperature cycling performance of NFPP positive electrode material is solved. The problem has significantly improved the performance of sodium ion batteries.
Patent Information
- Application Number
- CN202411390154.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The low energy density and low temperature cycle performance of sodium ferric pyrophosphate (NFPP) cathode material has poor low energy density and low temperature cycling performance, which limits its development in the field of sodium ion batteries.
Using a positive electrode active material with a core and carbon coating chemical composition of Na4Fex(PO4)2(P2O7), the electron conductivity and sodium ion diffusion ability of the material are improved by spray drying and fluidized drying combined with the rotary kiln sintering process. .
It significantly improves the energy density and low-temperature cycling performance of sodium ion batteries, and improves the structural stability and electrochemical performance of the material.
Smart Images

Figure CN119153660A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium ion batteries and relates to a positive electrode active material, in particular to a positive electrode active material and a preparation method and application thereof. Background Art
[0002] With the deepening of research on sodium electric materials, sodium iron pyrophosphate (NFPP) cathode material has attracted much attention in the energy storage market due to its high structural stability and wide selection of synthetic raw materials, and is expected to become the next generation of energy storage cathode material. However, the low energy density of NFPP cathode material has greatly limited its application. At present, the energy density of the battery is generally improved by increasing the working voltage of the sodium ion battery or the compaction density of the cathode sheet, but the improvement is limited; and the low-temperature cycle performance of the cathode material is also poor, which seriously hinders the development of sodium iron pyrophosphate in the battery field.
[0003] Therefore, how to further improve the sodium iron pyrophosphate (NFPP) positive electrode material to improve the energy density and low-temperature cycle performance of sodium ion batteries is an urgent problem to be solved in this field. Summary of the invention
[0004] In view of the above-mentioned defects, the present invention provides a positive electrode active material, which has a higher gram capacity, higher sodium ion diffusion capacity and electronic conductivity, and can effectively improve the energy density and low-temperature cycle performance of the battery.
[0005] The present invention also provides a method for preparing the above-mentioned positive electrode active material. The positive electrode active material prepared by the preparation method not only has a higher gram capacity, but also has a higher sodium ion diffusion capacity and electronic conductivity, so that the sodium ion battery can have a higher energy density and low-temperature cycle performance.
[0006] The present invention also provides a positive electrode sheet, comprising the positive electrode active material or the positive electrode active material prepared by the above preparation method. The positive electrode sheet is applied to a sodium ion battery to effectively improve the energy density and low-temperature cycle performance of the battery.
[0007] The present invention provides a sodium ion battery, comprising the above-mentioned positive electrode active material, or the positive electrode active material prepared by the above-mentioned preparation method, or the above-mentioned positive electrode sheet, so that the sodium ion battery has higher energy density and low-temperature cycle performance.
[0008] The present invention provides a positive electrode active material, the positive electrode active material comprising a core and a carbon coating layer arranged on at least a portion of the surface of the core, the core comprising a chemical composition shown in Formula 1, Na4Fe x (PO4)2(P2O7) Formula 1
[0009] In formula 1, 2.8≤x≤3.0;
[0010] In the X-ray diffraction pattern of the positive electrode active material, there is a first diffraction peak at 2θ of 33.6°, and a second diffraction peak at 2θ of 32.9°, and the ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is greater than 22.5.
[0011] Furthermore, the mass percentage content C of the carbon coating layer in the positive electrode active material is 1.50wt%-2.15wt%.
[0012] Furthermore, the median particle size D50 of the positive electrode active material is 8 μm-10 μm, and the specific surface area of the positive electrode active material is not higher than 13.5 m 2 / g.
[0013] Furthermore, the positive electrode active material satisfies any one of Formula 2, Formula 3, and Formula 4,
[0014] 1.5%<C<1.7% and 8.5<BET<10.5 Formula 2;
[0015] 1.7%≤C<1.9% and 10.5≤BET<11.5 Formula 3;
[0016] 1.9%≤C<2.15% and 11.5≤BET<13.5 Formula 4.
[0017] Furthermore, the powder compaction density of the positive electrode active material is 1.91-2.01 g / cm 3 .
[0018] Furthermore, the positive electrode active material also includes a doping element;
[0019] The doping element includes at least one of B, F, Al, and N.
[0020] Furthermore, the mass percentage of the doping element in the positive electrode active material is 500ppm-2000ppm.
[0021] The present invention also provides a method for preparing the positive electrode active material described in any one of the above, comprising the following steps:
[0022] 1) mixing raw materials including a sodium source, an iron source, a phosphorus source, and a carbon source with deionized water to obtain a mixture; grinding the mixture to obtain a grind; the grind has a D10 of 0.10 μm-2 μm, a D50 of 0.25 μm-0.3 μm, and a D90 of 0.7 μm-1.0 μm;
[0023] 2) spray drying the ground material to obtain a spray material; the spray material has a water content of ≤3% and a bulk density of ≤0.8 g / cm 3 ;
[0024] 3) subjecting the spray material to fluidized drying treatment, during which: the fluidization temperature is 600° C.-1000° C., the gas flow rate is 5-20 m / s, and the fluidization time is 3-5 s to obtain a fluidized material;
[0025] 4) Under a protective atmosphere, using a rotary kiln, sequentially performing a first sintering and a second sintering on the fluidized material to obtain the positive electrode active material;
[0026] The temperature of the first sintering is 200-250° C., and the holding time is 1-2 hours; the temperature of the second sintering is 400-550° C., and the holding time is 10-20 hours.
[0027] Further, in step 1), grinding is performed by ball milling;
[0028] The grinding comprises: performing first grinding and second grinding on the mixed material in sequence to obtain the grinding material; the first grinding has a rotation speed of 1000-1300 r / min, a grinding time of 30-50 min, and a particle size of the grinding beads of 0.6-0.8 μm; the second grinding has a rotation speed of 1400-1600 r / min, a grinding time of 30-60 min, and a particle size of the grinding beads of 0.3-0.4 μm;
[0029] And / or, in step 2), the inlet air temperature during the spray drying process is 175-205°C, the outlet air temperature is 80-110°C, and the difference between the inlet air temperature and the outlet air temperature is 95-105°C.
[0030] The present invention also provides a positive electrode sheet, comprising any one of the positive electrode active materials described above, or the positive electrode active material prepared by the above preparation method.
[0031] The present invention also provides a sodium ion battery, comprising any one of the positive electrode active materials, or the positive electrode active material prepared by the above preparation method, or the above positive electrode sheet.
[0032] The present invention provides a positive electrode active material comprising a chemical composition of Na4Fe xThe core of (PO4)2(P2O7) and the carbon coating layer located on at least a portion of the surface of the core, while making the peak intensity ratio of the first diffraction peak located at 33.6° and the second diffraction peak located at 32.9° in the X-ray diffraction pattern of the positive electrode active material greater than 22.5, effectively improve the gram capacity of the positive electrode active material, and improve its electronic conductivity and sodium ion mobility, thereby effectively improving the energy density and low-temperature cycle performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a SEM image of the fluidized material in Example 1 of the present invention;
[0034] Figure 2 This is a SEM image of the positive electrode active material in Example 1 of the present invention at 1.00K;
[0035] Figure 3 This is a SEM image of the positive electrode active material at 1.00K in Example 3 of the present invention;
[0036] Figure 4 This is a SEM image of the positive electrode active material at 30.0 K in Example 3 of the present invention;
[0037] Figure 5 This is a SEM image of the positive electrode active material in Comparative Example 8 of the present invention at 30.0K;
[0038] Figure 6 This is the XRD spectrum of the positive electrode active material in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] A first aspect of the present invention provides a positive electrode active material, the positive electrode active material comprising a core and a carbon coating layer disposed on at least a portion of the surface of the core, the core comprising a chemical composition shown in Formula 1,
[0041] Na4Fe x (PO4)2(P2O7) Formula 1
[0042] In formula 1, 2.8≤x≤3.0;
[0043] In the X-ray diffraction pattern of the positive electrode active material, there is a first diffraction peak at 2θ of 33.6°, a second diffraction peak at 2θ of 32.9°, and the ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is greater than 22.5.
[0044] Furthermore, the positive electrode active material in the present invention is a polycrystalline positive electrode material.
[0045] The X-ray diffraction pattern of the positive electrode active material in the present invention is obtained by performing an XRD test on the positive electrode active material and refining the X-ray diffraction spectrum obtained by the test, the refinement coefficient Rwp<9, and the test parameters are: the radiation line is a Cu target, Kα rays, the wavelength is 0.154056nm, the scanning angle range is 10°-80°, the scanning rate is 5° / min, and the step length is 0.0065°.
[0046] The present invention provides a positive electrode active material comprising a core and a carbon coating layer located on at least a portion of the outer surface of the core, and the core comprises a chemical composition of Na4Fe x (PO4)2(P2O7), wherein 2.8≤x≤3, can effectively improve the electronic conductivity of the positive electrode active material; at the same time, the positive electrode active material is an iron-deficient phase, which can significantly improve the diffusion rate of sodium ions, thereby effectively improving the charge and discharge performance of the sodium ion battery, so that it has a higher low-temperature cycle performance; at the same time, in the X-ray diffraction pattern of the positive electrode active material, there is a first diffraction peak at 2θ of 33.6°, a second diffraction peak at 2θ of 32.9°, and the first diffraction peak is 2θ. The ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is greater than 22.5, wherein the first diffraction peak is the characteristic main peak of sodium ferric phosphate pyrophosphate (NFPP), and the second diffraction peak is the characteristic impurity peak of sodium ferric phosphate of nitrosodium phosphate structure, and sodium ferric phosphate has no electrochemical activity. When the ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is greater than 22.5, the content of sodium ferric phosphate impurity phase in the positive electrode active material is low and the purity is high, which can effectively increase the gram capacity of the positive electrode active material, thereby effectively improving the energy density of the sodium ion battery.
[0047] In addition, since the content of sodium iron phosphate impurity phase in the positive electrode active material of the present invention is relatively low, the occurrence of side reactions between the positive electrode active material and the electrolyte can be effectively suppressed, which helps to improve the cycle performance and safety of the battery.
[0048] In a specific embodiment, the mass percentage C of the carbon coating layer in the positive electrode active material is 1.50wt%-2.15wt%. Within this range, the positive electrode active material not only has a higher electronic conductivity and powder compaction density, but also can reduce the energy density loss caused by inactive carbon, further improving the energy density and low-temperature cycle performance of the battery.
[0049] Exemplarily, the mass percentage C of the carbon coating layer in the positive electrode active material is 1.50wt%, 1.55wt%, 1.60wt%, 1.65wt%, 1.70wt%, 1.75wt%, 1.80wt%, 1.85wt%, 1.90wt%, 1.95wt%, 2.00wt%, 2.05wt%, 2.10wt% or 2.15wt%.
[0050] The mass percentage of the carbon coating layer in the positive electrode active material in the present invention can be obtained by testing with an element analyzer.
[0051] In a specific embodiment, the median particle size D50 of the positive electrode active material is 8 μm-10 μm, and the specific surface area of the positive electrode active material is not higher than 13.5 m 2 / g. Within this range, the positive electrode active material has a higher powder compaction density, which is beneficial to improving the energy density of the battery; and the carbon coating layer is more evenly coated, which can further improve the conductivity of the positive electrode active material and make the battery have higher low-temperature cycle performance; in addition, the specific surface area of the positive electrode active material is low, which can effectively reduce the side reaction between the electrolyte and the positive electrode, thereby effectively improving the cycle performance of the battery.
[0052] D50 in the present invention refers to the particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 50%, which can be obtained by testing with a laser particle size analyzer.
[0053] In a specific embodiment, the positive electrode active material satisfies any one of Formula 2, Formula 3, and Formula 4,
[0054] 1.5%<C<1.7% and 8.5<BET<10.5 Formula 2;
[0055] 1.7%≤C<1.9% and 10.5≤BET<11.5 Formula 3;
[0056] 1.9%≤C<2.15% and 11.5≤BET<13.5 Formula 4.
[0057] When the positive electrode active material satisfies any one of the above formulas 2, 3, and 3, the coating effect of the carbon coating layer is better and more uniform, which is beneficial to improving the electronic conductivity of the positive electrode active material; at the same time, it can further reduce the loss of energy density caused by inactive carbon, thereby making the sodium ion battery have higher low-temperature cycle performance and energy density.
[0058] In one embodiment, the powder compaction density of the positive electrode active material is 1.91-2.01 g / cm 3 For example, the compacted density is 1.91 g / cm 3 、1.92g / cm 3, 1.93g / cm 3 , 1.94g / cm 3 , 1.95g / cm 3 , 1.96g / cm 3 , 1.97g / cm 3 、1.98g / cm 3 , 1.99g / cm 3 , 2.00g / cm 3 or 2.01g / cm 3 Within this range, the powder compaction density of the positive electrode active material is high, and a higher compaction density can be achieved, thereby further improving the energy density of the sodium ion battery.
[0059] The compacted density of the powder in the present invention is obtained by testing at a pressure of 1 T (equivalent to 74.0 MPa).
[0060] In a specific embodiment, the positive electrode active material further includes a doping element; the doping element includes at least one of B, F, Al, and N.
[0061] It should be noted that the aforementioned doping elements are coated on the surface of the carbon coating layer.
[0062] When the positive electrode active material also includes the aforementioned doping elements, on the one hand, the structural stability of the positive electrode active material can be improved, the voltage of the positive electrode active material can be increased, and the capacity can be fully utilized during the charge and discharge process; on the other hand, it can effectively solve the problems of low ball formation rate and easy breakage of particles during spray drying, improve the regularity of the morphology of the positive electrode active material particles, and reduce the side reactions between the electrolyte and the positive electrode, thereby further improving the energy density and cycle stability of the sodium ion battery.
[0063] In a specific embodiment, the mass percentage of the doping element in the positive electrode active material is 500ppm-2000ppm. Within this range, not only can the structural stability and morphological regularity of the positive electrode active material be further improved, but also the problem of reduced charge and discharge capacity due to excessive doping can be avoided.
[0064] Illustratively, the mass percentage of the doping element in the positive electrode active material is 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm or 2000ppm.
[0065] The mass percentage of the doping element in the present invention can be obtained by testing with an inductively coupled plasma optical emission spectrometer (ICP-OES Avio200 / Avio500).
[0066] The second aspect of the present invention provides a method for preparing the positive electrode active material of the first aspect, comprising the following steps:
[0067] 1) mixing raw materials including a sodium source, an iron source, a phosphorus source, and a carbon source with deionized water to obtain a mixture; grinding the mixture to obtain a grind; the grind has a D10 of 0.10 μm-2 μm, a D50 of 0.25 μm-0.3 μm, and a D90 of 0.7 μm-1.0 μm;
[0068] 2) The ground material is spray-dried to obtain a spray material; the water content of the spray material is ≤3%, and the bulk density is ≤0.8g / cm 3 ;
[0069] 3) subjecting the spray material to fluidized drying treatment, during which: the fluidization temperature is 600° C.-1000° C., the gas flow rate is 5-20 m / s, and the fluidization time is 3-5 s to obtain a fluidized material;
[0070] 4) Under a protective atmosphere, using a rotary kiln, sequentially sintering the fluidized material through a first sintering and a second sintering to obtain a positive electrode active material;
[0071] The temperature of the first sintering is 200-250°C, and the holding time is 1-2h; the temperature of the second sintering is 400-550°C, and the holding time is 10-20h.
[0072] Specifically, in step 1), raw materials including a sodium source, an iron source, a phosphorus source, and a carbon source are added to deionized water and uniformly mixed to obtain a mixture; the mixture is then ground to obtain a ground material having a D10 of 0.10 μm-2 μm, a D50 of 0.25 μm-0.3 μm, and a D90 of 0.7 μm-1.0 μm. At this time, the particle size distribution of the ground material is more uniform, which is conducive to improving the ball formation rate in the subsequent spray drying process, improving the uniformity of carbon coating, and at the same time being conducive to the capacity of the positive electrode active material.
[0073] The sodium source in the present invention refers to a raw material that provides the sodium element, the iron source refers to a raw material that provides the iron element, the phosphorus source refers to a raw material that provides the phosphorus element, and the carbon source refers to a raw material that provides the carbon element. As long as the target element (Na, Fe, P, C) is contained, it falls within the definition of the present invention, and one target element can be introduced into the reaction system through one or more raw materials. For example, iron phosphate can be used as both an iron source and a phosphorus source, and sodium pyrophosphate can be used as both a sodium source and a phosphorus source.
[0074] The present invention does not specifically limit the specific types of the sodium source, iron source, phosphorus source, and carbon source. For example, the sodium source includes at least one of sodium carbonate, sodium pyrophosphate, sodium dihydrogen phosphate, sodium acetate, disodium dihydrogen pyrophosphate, ammonium dihydrogen phosphate, and sodium phosphate; the iron source includes at least one of iron oxide, ferric phosphate, ferrous oxalate, iron powder, ferric acetate, and ferric nitrate; the phosphorus source includes at least one of ferric phosphate, sodium pyrophosphate, sodium dihydrogen phosphate, phosphoric acid, and disodium hydrogen phosphate; and the carbon source includes at least one of glucose, vitamin C, citric acid, Tween 60, sucrose, polyethylene glycol 2000, and oxalic acid.
[0075] The present invention does not impose any specific restrictions on the molar ratio of the sodium source, the iron source, and the phosphorus source. It is only necessary that the chemical composition of the core in the prepared positive electrode active material satisfies Formula 1.
[0076] The present invention does not specifically limit the mass percentage of the carbon source in the raw material. Furthermore, the mass percentage of the carbon coating layer in the positive electrode active material can be further controlled by controlling the amount of the carbon source added.
[0077] The present invention does not specifically limit the specific sources of the sodium source, iron source, phosphorus source, and carbon source, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0078] The present invention does not specifically limit the mixing method, and the mixed materials only need to be mixed uniformly, for example, the mixing can be carried out by mechanical stirring.
[0079] The solid content of the mixture of the present invention is not specifically limited, for example, the solid content is 15wt%-35wt%.
[0080] The present invention does not specifically limit the grinding method, and it is only necessary to make the D10, D50, and D90 of the grinding material within the aforementioned ranges.
[0081] D10 in the present invention refers to the particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 10%, D50 refers to the particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 50%, and D90 refers to the particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 90%.
[0082] In step 2), the above-mentioned ground material is spray-dried to obtain a water content of ≤3% and a bulk density of ≤0.8g / cm 3 At this time, it helps to evaporate the water during the fluidized drying process, avoids the carbon corrosion problem caused by water in the subsequent sintering process, and improves the uniformity of the carbon coating layer; at the same time, it helps the initial formation of crystal nuclei and the initial coating of carbon sources during the fluidization process, which is beneficial to the further growth of crystals and the effective coating of carbon sources in the subsequent sintering process.
[0083] Furthermore, the median particle size D50 of the spray material can be further controlled so that the median particle size D50 of the positive electrode active material is between 8 μm and 10 μm; preferably, the median particle size D50 of the spray material is between 8 μm and 10 μm.
[0084] Furthermore, the ball formation rate of the spray material is not less than 95%.
[0085] The balling rate in the present invention can be obtained by statistically importing the SEM image at 30K using Nano Measurer software.
[0086] The present invention does not impose any specific restrictions on the air inlet temperature and air outlet temperature during the spray drying process. It is only necessary that the water content and bulk density of the prepared spray material meet the aforementioned ranges.
[0087] In step 3), the spray material is subjected to fluidized drying treatment, the fluidization temperature is maintained at 600°C-1000°C, the gas flow rate is 5-20m / s, and the fluidization time is 3-5s to obtain a fluidized material. In this process, on the one hand, the water in the spray material can be fully evaporated to prevent the water from corroding the carbon coating layer during the subsequent sintering process and affecting the carbon coating effect; on the other hand, the spray material can undergo a preliminary reaction to generate crystal nuclei, improve the reaction activity, and contribute to the growth of the positive electrode active material during the subsequent sintering process, so that the elements are distributed more evenly and the uniformity of the carbon coating layer is improved.
[0088] Exemplarily, the fluidizing temperature is 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C; the gas flow rate is 5m / s, 8m / s, 11m / s, 14m / s, 17m / s or 20m / s; the fluidizing time is 3s, 4s or 5s
[0089] The present invention does not specifically limit the gas used in the fluidized drying process, and may be, for example, argon and / or nitrogen.
[0090] In step 4), a rotary kiln is used to first sinter the fluidized material at 200-250°C in a protective atmosphere for 1-2 hours, and then a second sintering is performed at 400-550°C for 10-20 hours to prepare a positive electrode active material. In this process, the metal elements grow rapidly along the crystal nucleus and crystal plane, and a uniform carbon coating layer is formed to obtain a positive electrode active material.
[0091] Illustratively, the temperature of the first sintering is 200° C., 210° C., 220° C., 230° C., 240° C. or 250° C.; and the holding time of the first sintering is 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h.
[0092] Illustratively, the temperature of the second sintering is 400° C., 430° C., 460° C., 490° C., 520° C. or 550° C.; and the holding time of the second sintering is 10 h, 12 h, 14 h, 16 h, 18 h or 20 h.
[0093] The present invention does not specifically limit the protective atmosphere. For example, nitrogen and / or argon can be used as the protective atmosphere.
[0094] Furthermore, the furnace pressure M (MPa) and the sintering capacity T (tons) during the sintering process satisfy any one of Formula 5, Formula 6, and Formula 7.
[0095] 0<T<1 ton, then M>80MPa Formula 5
[0096] 1≤T<3 tons, then 60MPa<M≤80MPa Formula 6
[0097] T≥3 tons, then 50MPa<M≤60MPa, formula 7.
[0098] The furnace pressure M in the present invention refers to the pressure in the rotary kiln, and the sintering capacity T refers to the feed amount in a unit rotary kiln.
[0099] Since the reaction occurring during the sintering process will produce gas and affect the furnace pressure, it is necessary to set the corresponding furnace pressure according to the feed amount in the unit kiln in order to stably produce uniform positive electrode active materials. When the furnace pressure and sintering capacity in the rotary kiln meet the above relationship, the uniformity of the performance of the positive electrode active materials can be improved.
[0100] The preparation method of the positive electrode active material of the present invention comprises the following steps: firstly, grinding to obtain a grinding material with uniform particle size distribution, thereby improving the ball forming rate in the spray drying process; secondly, spray drying the grinding material to obtain a water content of ≤3% and a bulk density of ≤0.8 g / cm 3 The spray material is helpful for the evaporation of water during the fluidized drying process and the initial formation of crystal nuclei and carbon coating layers; then, the spray material is subjected to fluidized drying treatment, and the fluidization temperature, gas flow rate and fluidization time are controlled, so that the metal elements in the spray material are initially reacted to form crystal nuclei, and at the same time, part of the carbon source is coked and coated on at least part of the outer surface of the spray material particles to obtain a fluidized material; then, the fluidized material is heat-insulated and sintered at two temperatures for a period of time, so that the metal elements grow rapidly along the crystal nuclei, and the carbon source is completely coked and coated on the particle surface, so as to obtain a positive electrode active material with a core-shell structure, and the core has Na4Fe xThe positive electrode active material has a chemical composition of (PO4)2(P2O7)(2.8≤x≤3.0), a shell layer is a carbon coating layer, and in the X-ray diffraction pattern of the positive electrode active material, there is a first diffraction peak at 2θ of 33.6°, and a second diffraction peak at 2θ of 32.9°, and the ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is greater than 22.5; therefore, the positive electrode active material not only has high electronic conductivity and sodium ion diffusion rate, but also has a low content of sodium iron phosphate impurity phase and high purity, which can effectively improve the gram capacity of the positive electrode active material, so that the sodium ion battery including the positive electrode active material has high energy density and low-temperature cycle performance.
[0101] In addition, since the preparation method of the present invention performs fluidized drying treatment before sintering, it saves the time of crystal nucleus formation during the sintering process, shortens the sintering cycle, and reduces the sintering temperature compared to the traditional sintering process, thereby achieving the purpose of reducing costs and increasing efficiency; and compared with roller kiln sintering, the present invention uses a rotary kiln for sintering, which can make the fluidized material heated more evenly, can effectively improve the uniformity of the metal element reaction, improve the electrochemical properties of the positive electrode active material, and save production consumables such as saggers used in roller kiln sintering, thereby reducing production energy consumption and costs; at the same time, the heating environment in the rotary kiln of the present invention can be provided by the airflow heat in the fluidized drying treatment, further reducing costs.
[0102] In a specific embodiment, grinding includes: in step 1), grinding by ball milling; grinding includes: subjecting the mixed material to first grinding and second grinding in sequence to obtain a grinding material; the first grinding speed is 1000-1300r / min, the grinding time is 30-50min, and the particle size of the grinding beads is 0.6-0.8μm; the second grinding speed is 1400-1600r / min, the grinding time is 30-60min, and the particle size of the grinding beads is 0.3-0.4μm. When the above grinding method is used, the particle size distribution of the grinding material can be further made more uniform, thereby further improving the ball formation rate during the spray drying process.
[0103] Exemplarily, the rotation speed of the first grinding is 1000r / min, 1050r / min, 1100r / min, 1150r / min, 1200r / min, 1250r / min or 1300r / min; the time of the first grinding is 30min, 35min, 40min, 45min or 50min; the particle size of the ball milling beads in the first grinding is 0.6μm, 0.7μm or 0.8μm.
[0104] Exemplarily, the rotation speed of the second grinding is 1400r / min, 1450r / min, 1500r / min, 1550r / min or 1600r / min; the time of the second grinding is 30min, 35min, 40min, 45min, 50min, 55min or 60min; the particle size of the ball milling beads in the second grinding is 0.3μm or 0.4μm.
[0105] In a specific embodiment, the air inlet temperature during the spray drying process is 175-205° C., the air outlet temperature is 80-110° C., and the difference between the air inlet temperature and the air outlet temperature is 95-105° C. At this time, the ball formation rate of the spray material can be further improved, and the D50, water content and bulk density of the spray material can be reduced, which is conducive to improving the powder compaction density of the positive electrode active material and the uniformity of the carbon coating layer, thereby improving the energy density and low-temperature cycle performance of the battery.
[0106] Exemplarily, the inlet air temperature is 175°C, 180°C, 185°C, 190°C, 195°C, 200°C or 205°C; the outlet air temperature is 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C.
[0107] In a specific embodiment, the raw material further includes a dopant, and the dopant includes at least one of Al2O3, NaBF4, and oleylamine. The structural stability of the prepared positive electrode active material can be effectively improved, the morphological regularity of the particles can be improved, the capacity can be exerted during the charge and discharge process, the side reaction between the electrolyte and the positive electrode can be reduced, and the cycle performance of the sodium ion battery can be improved.
[0108] The present invention does not specifically limit the mass percentage of the dopant in the raw material. Furthermore, the mass percentage of the doping element in the positive electrode active material can be further controlled to be 500ppm-2000ppm by controlling the mass content of the dopant in the raw material.
[0109] The third aspect of the present invention provides a positive electrode sheet, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect. Since the positive electrode active material included therein has high electronic conductivity and sodium ion mobility, and also has high gram capacity, the positive electrode sheet is used in a sodium ion battery, which can effectively improve the energy density and low temperature cycle performance of the battery.
[0110] The fourth aspect of the present invention provides a sodium ion battery, comprising the positive electrode active material of the first aspect, or the positive electrode active material prepared by the preparation method of the second aspect, or the positive electrode sheet of the third aspect. Therefore, the sodium ion battery has a high energy density and low temperature cycle performance.
[0111] Hereinafter, the positive electrode active material of the present invention is described in detail through specific examples.
[0112] Example 1
[0113] 1) mixing raw materials including sodium carbonate, ferric phosphate, glucose, aluminum oxide, and sodium tetrafluoroborate, wherein the molar ratio of the sodium source, the iron source, and the phosphorus source is 1:0.7:1, and the mass percentage of the carbon source in the raw materials is 10wt%, adding into deionized water, mixing evenly, and obtaining a mixture with a solid content of 30wt%; performing a first grinding of the mixture at 1200r / min, the grinding time is 50min, and the particle size of the grinding beads is 0.7μm, and then performing a second grinding at 1400r / min, the grinding time is 60min, and the particle size of the grinding beads is 0.3μm, and obtaining a grinding material with D10 of 0.25μm, D50 of 0.29μm, and D90 of 0.85μm;
[0114] 2) The above-mentioned ground material was spray dried, and the air inlet temperature was set to 200°C and the air outlet temperature was set to 105°C, and the median particle size D50 was 9 μm, the water content was 2%, and the bulk density was 0.7 g / cm 3 Spray material;
[0115] 3) The spray material is subjected to fluidized drying treatment, and the fluidization temperature is set to 800°C and the gas flow rate is 17Nm 3 / s, the fluidization time is 3s, and the fluidized material is obtained; Figure 1 As shown, it is a SEM image of the fluidized material. It can be seen from the figure that the surface of the fluidized material is smoother and more regular, which is conducive to improving the uniformity of the carbon coating layer;
[0116] 4) Under nitrogen atmosphere, the fluidized material was transferred into a rotary kiln for first sintering and second sintering in sequence. The temperature of the first sintering was set to 200°C and the holding time was 2h. The temperature of the second sintering was set to 500°C and the holding time was 11h. The positive electrode active material of this embodiment was obtained. The core chemical composition of the core was Na4Fe 2.8 (PO4)2(P2O7), the doping amount of Al is 800ppm, and the doping amount of B is 1000ppm; the mass content of the carbon coating layer in the positive electrode active material measured by an element analyzer is 1.95wt%.
[0117] Example 2
[0118] 1) mixing raw materials including sodium carbonate, ferric phosphate, glucose, aluminum oxide, and sodium tetrafluoroborate, wherein the molar ratio of the sodium source, the iron source, and the phosphorus source is 1:0.725:1, and the mass percentage of the carbon source in the raw materials is 7wt%, adding into deionized water, mixing evenly, and obtaining a mixture with a solid content of 30wt%; performing a first grinding of the mixture at 1100r / min, the grinding time is 40min, and the particle size of the grinding beads is 0.8μm, and then performing a second grinding at 1500r / min, the grinding time is 40min, and the particle size of the grinding beads is 0.3μm, and obtaining a grinding material with D10 of 1.2μm, D50 of 0.22μm, and D90 of 0.91μm;
[0119] 2) The above-mentioned ground material was spray dried, and the air inlet temperature was set to 205°C and the air outlet temperature was set to 100°C, and the median particle size D50 was 8 μm, the water content was 1%, and the bulk density was 0.6 g / cm 3 Spray material;
[0120] 3) The spray material is subjected to fluidized drying treatment, and the fluidization temperature is set to 600°C and the gas flow rate is 5Nm 3 / s, the fluidization time is 5s, and the fluidized material is obtained;
[0121] 4) Under nitrogen atmosphere, the fluidized material was transferred into a rotary kiln for first sintering and second sintering in sequence. The temperature of the first sintering was set to 250°C and the holding time was 1 hour. The temperature of the second sintering was set to 400°C and the holding time was 20 hours. The positive electrode active material of this embodiment was obtained. The core chemical composition of the core was Na4Fe 2.9 (PO4)2(P2O7), the doping amount of Al is 800ppm, and the doping amount of B is 1000ppm; the mass content of the carbon coating layer in the positive electrode active material measured by an element analyzer is 1.52wt%.
[0122] Example 3
[0123] 1) mixing raw materials including sodium carbonate, ferric phosphate, glucose and alumina, wherein the molar ratio of the sodium source, the iron source and the phosphorus source is 1:0.7:1, and the mass percentage of the carbon source in the raw materials is 11wt%, adding into deionized water, mixing evenly, and obtaining a mixture with a solid content of 30wt%; performing a first grinding of the mixture at 1000r / min, the grinding time is 30min, the particle size of the grinding beads is 0.8μm, and then performing a second grinding at 1600r / min, the grinding time is 30min, the particle size of the grinding beads is 0.4μm, and obtaining a grinding material with D10 of 1.9μm, D50 of 0.28μm and D90 of 0.96μm;
[0124] 2) The above-mentioned ground material was spray dried, and the air inlet temperature was set to 205°C and the air outlet temperature was set to 100°C, and the median particle size D50 was 8 μm, the water content was 1%, and the bulk density was 0.6 g / cm 3 Spray material;
[0125] 3) The spray material is subjected to fluidized drying treatment, and the fluidization temperature is set to 1000°C and the gas flow rate is 20Nm 3 / s, the fluidization time is 4s, and the fluidized material is obtained;
[0126] 4) Under nitrogen atmosphere, the fluidized material was transferred into a rotary kiln for first sintering and second sintering in sequence. The temperature of the first sintering was set to 240°C and the holding time was 1.5 h. The temperature of the second sintering was set to 450°C and the holding time was 15 h. The positive electrode active material of this embodiment was obtained. The core chemical composition of the material was Na4Fe 2.9 (PO4)2(P2O7), the Al doping amount is 800ppm; the mass content of the carbon coating layer in the positive electrode active material measured by an element analyzer is 2.15wt%.
[0127] Example 4
[0128] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the raw material does not include aluminum oxide, and the mass content of the carbon coating layer in the positive electrode active material measured by an element analyzer is 1.89wt%.
[0129] Example 5
[0130] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Example 1, except that in step 1), the aluminum oxide in the raw material is replaced by oleylamine, and the doping amount of the doping element N in the prepared positive electrode active material is 1000ppm, and the doping amount of B is 1000ppm; the mass content of the carbon coating layer in the positive electrode active material measured by an element analyzer is 2.03wt%.
[0131] Example 6
[0132] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 3, except that in step 1), the mass percentage of the carbon source in the raw material is adjusted to 12wt%, and the other contents remain unchanged. The mass content of the carbon coating layer in the positive electrode active material measured by an element analyzer is 2.27wt%.
[0133] Example 7
[0134] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 3, except that the content of aluminum oxide in the raw material is adjusted so that the mass percentage of the doping element in the positive electrode active material is 400 ppm.
[0135] Example 8
[0136] The preparation method of the positive electrode active material in this embodiment is basically the same as that in Embodiment 3, except that the content of aluminum oxide in the raw material is adjusted so that the mass percentage of the doping element in the positive electrode active material is 2100 ppm.
[0137] Comparative Example 1
[0138] The preparation method of the positive electrode active material in this embodiment is basically the same as that in embodiment 3, except that in step 1), the molar ratio of the sodium source, the iron source, and the phosphorus source is adjusted to 1:0.675:1, and the chemical composition of the core of the prepared positive electrode active material is Na4Fe 2.7 (PO4)2(P2O7), the mass content of the carbon coating layer in the positive electrode active material was 1.93wt% as tested by an element analyzer.
[0139] Comparative Example 2
[0140] The preparation method of the extremely active material in this comparative example is basically the same as that in Example 3, except that in step 4), the temperature of the second sintering is adjusted to 600°C.
[0141] Comparative Example 3
[0142] The preparation method of the extremely active material in this comparative example is basically the same as that in Example 3, except that in step 1), the D10, D50 and D90 of the grinding material are adjusted to 0.27 μm, 0.38 μm and 1.10 μm.
[0143] Comparative Example 4
[0144] The preparation method of the active material in this comparative example is basically the same as that in Example 3, except that in step 2), the inlet air temperature is adjusted to 225°C and the outlet air temperature is adjusted to 115°C. At this time, the median particle size D50 is 11 μm, the water content is 3%, and the bulk density is 0.9 g / cm 3 of spray material.
[0145] Comparative Example 5
[0146] The preparation method of the active material in this comparative example is basically the same as that in Example 3, except that in step 3), the fluidization temperature is adjusted to 1100°C and the air flow rate is adjusted to 25 Nm 3 / s, the fluidization time is 2S.
[0147] Comparative Example 6
[0148] The preparation method of the extremely active material in this comparative example is basically the same as that in Example 3, except that the spray material is directly subjected to the first sintering and the second sintering without fluidized drying treatment.
[0149] Comparative Example 7
[0150] The preparation method of the extremely active material in this comparative example is basically the same as that in Example 3, except that in step 4), the temperature of the first sintering is adjusted to 300°C and the holding time is adjusted to 3h; the temperature of the second sintering is adjusted to 560°C and the holding time is adjusted to 9h.
[0151] Comparative Example 8
[0152] The preparation method of the extremely active material in this comparative example is basically the same as that in Example 3, except that in step 4), the rotary kiln is adjusted to a roller kiln.
[0153] The basic parameters are shown in Table 1.
[0154] Table 1
[0155]
[0156]
[0157] Test example
[0158] 1. The positive electrode active materials prepared in Example 1 and Example 3 were subjected to SEM test. The test results are shown in Figure 2 and Figure 3 .
[0159] Figure 2 is the SEM image of the positive electrode active material in Example 1 at 1.00K, Figure 3 is the SEM image of the positive electrode active material in Example 3 at 1.00k. Figure 2 and Figure 3 It can be seen that the positive electrode active material without doping elements is partially broken and has a rough surface morphology, while the positive electrode active material in Example 3 contains doping elements, and its particle surface is relatively smooth and has a high sphericity. It can be seen that by doping elements into the positive electrode active material, the structural stability of the positive electrode active material can be effectively improved, the particle breakage problem can be improved, and the regularity of the particle morphology of the positive electrode active material can be improved.
[0160] 2. The positive electrode active materials prepared in Example 3 and Comparative Example 8 were subjected to SEM test. The test results are shown in Figure 4 and Figure 5 .
[0161] Figure 4is the SEM image of the positive electrode active material in Example 3 at 30.0K, Figure 5 is the SEM image of the positive electrode active material in Comparative Example 8 at 30.0k. Figure 4 and Figure 5 It can be seen that compared with the roller kiln, the surface of the positive electrode active material sintered in the rotary kiln is more regular and the carbon coating effect is better.
[0162] 3. XRD test was performed on the positive electrode active materials prepared in the above examples and comparative examples. The test results are shown in Tables 2 and Figure 6 .
[0163] Figure 6 is the XRD pattern of the positive electrode active material in Example 1, Figure 6 It can be seen that there is a first diffraction peak with a peak intensity of 1082 at 33.6°, and a second diffraction peak with a peak intensity of 33 at 32.9°, and the peak intensity ratio of the first diffraction peak to the second diffraction peak is 32.78, which is greater than 22.5.
[0164] Table 2
[0165]
[0166] From Table 2, we can see that:
[0167] The positive electrode active materials in Examples 1 to 8 have a first diffraction peak at 2θ of 33.6° and a second diffraction peak at 2θ of 32.9°, and the ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is greater than 22.5, while the peak intensity ratios of the positive electrode active materials in Comparative Examples 1 to 8 are less than 22.5.
[0168] 4. Testing the gram capacity, electronic conductivity and sodium ion mobility of the positive electrode active materials prepared in the above embodiments and comparative examples comprises the following steps:
[0169] The positive electrode active material, conductive carbon black Super P, and polyvinylidene fluoride (PVDF) prepared in the above embodiments and comparative examples were mixed in a mass ratio of 9:0.5:0.5, and ground evenly in an agate mortar, and then an appropriate amount of N-methylpyrrolidone (NMP) solvent was added to prepare a uniform slurry, and then the prepared slurry was evenly coated on a clean aluminum foil, baked at 110°C for 20 minutes, and then transferred to a 60°C vacuum oven for drying for 12 hours; the dried pole piece was cut into a circular pole piece with a diameter of 13 mm using a button battery slicer, and the surface density was 1.25 g / 100 cm 2 , compacted density is 2.00g / cm 3The positive electrode sheet of each electrode sheet was weighed and recorded, and finally the weighed electrode sheet was placed in a vacuum oven at 100℃ for 12 hours for assembly of button half-cells. The battery was assembled in a closed glove box filled with argon gas. The assembly order was negative electrode shell-positive electrode sheet-diaphragm-sodium sheet-gasket-spring sheet-electrolyte-positive electrode shell. The assembled battery was placed on a battery packaging machine for compression packaging, and then the battery was taken out of the glove box and left to stand for 24 hours before electrochemical testing.
[0170] 1) Gram capacity
[0171] The button battery prepared as above was subjected to charge and discharge tests with a test voltage of 2-3.4 V and a test condition of 0.2C to obtain a charge and discharge curve. The discharge capacity in grams of the battery was calculated based on the discharge curve. Discharge capacity in grams (mAh / g) = discharge current (mA) × discharge time (h) / battery mass (g).
[0172] 2) Electronic conductivity
[0173] The button cell prepared above was subjected to cyclic voltammetry test using the AutoLab electrochemical workstation of Metrohm. The test voltage range was 2V-3.4V. The initial voltage and the termination voltage were both the open circuit voltage of the cell. The scanning direction was from low voltage to high voltage. The scanning rates were 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1 mV·s. -1 , the electronic conductivity is obtained by testing.
[0174] 3) Sodium ion mobility
[0175] The button battery prepared above was subjected to AC impedance test using the Autolab electrochemical workstation of Metrohm, Switzerland. The test frequency range was 105-10-2 Hz and the amplitude was 10 mV. The test data was fitted using the Autolab software Nova2.1 to obtain the corresponding circuit elements and the corresponding impedance values for conversion to obtain the sodium ion mobility.
[0176] The test results are shown in Table 3.
[0177] 2. The positive electrode active materials prepared in the above embodiments and comparative examples are made into sodium ion batteries, and the specific steps include:
[0178] The positive electrode active material, conductive carbon black Super P, carbon nanotubes, polyvinylidene fluoride (PVDF, 7% 5130 binder), and dispersant polyvinyl pyrrolidone (PVP) prepared in the above examples and comparative examples were mixed in a mass ratio of 93:3.2:0.1:3.5:0.2, and then an appropriate amount of N-methylpyrrolidone (NMP) solvent was added to prepare a uniform slurry. The prepared slurry was then evenly coated on a clean aluminum foil, baked at 110°C for 20 minutes, and then transferred to a vacuum oven at 60°C for drying for 12 hours. After rolling and slitting, a surface density of 12.5 mg / cm 2 , compacted density is 1.8g / cm 3 The positive electrode sheet. Hard carbon (Kuraray Type 2), conductive carbon black Super P, carbon nanotubes, and polyvinylidene fluoride (PVDF, 5% 5130 binder) were uniformly mixed in a mass ratio of 93:1.9:0.1:5, deionized water was added, and the negative electrode slurry was obtained after uniform mixing. Then, the negative electrode slurry was evenly coated on a clean copper foil, baked at 110°C for 20 minutes, and then transferred to a vacuum oven at 60°C for drying for 12 hours. After rolling and slitting, the surface density of 5 mg / cm 2 , compacted density is 0.9g / cm 3 A negative electrode sheet. A 16μm aluminum foil is used as a separator, and the electrolyte includes sodium hexafluorophosphate sodium salt and an organic solvent. The organic solvent includes ethyl methyl carbonate, diethyl carbonate, vinylene carbonate, propylene carbonate, 1,3-propane sultone and ethyl acetate in a volume ratio of 52.51:0.60:1.78:22.18:1.55:21.38, and the molar concentration of the sodium salt is 1M; the positive electrode sheet, separator, and negative electrode sheet are assembled into a battery cell, and a sodium ion battery is obtained after baking, liquid injection, formation, and capacity division, and the NP ratio (ratio of negative electrode capacity to positive electrode capacity) is 1.2. The formation adopts the following steps:
[0179] First cycle: charge at 0.05C for 1h, 0.1C for 1h, 0.2C to 3.4V, then charge at 0.05C constant voltage, and then discharge at 0.1C to 2.0V;
[0180] Second cycle: charge to 3.4V at 0.2C, then charge at 0.05C constant voltage, and then discharge to 2.0V at 0.2C;
[0181] The third cycle: charge to 3.4V at 1C, then maintain constant voltage at 0.05C, and then discharge to 2.0V at 1C, and the formation is complete.
[0182] The energy density and low temperature cycle performance of the sodium ion battery prepared above were tested:
[0183] 1) Energy density
[0184] Before the test, the positive electrode active material in the above sodium ion battery was weighed in g. Then the sodium ion battery was charged at a constant current of 0.33C with a cut-off voltage of 3.4V, and then discharged at a constant current of 0.33C with a cut-off voltage of 2V. The actual discharge capacity of the battery was measured in Ah, and the discharge voltage of the battery was recorded in V. The ratio of the product of the discharge voltage and the capacity to the mass of the active material is the mass energy density of the sodium ion battery in Wh / kg.
[0185] 2) Low temperature cycle performance
[0186] At 25°C, the sodium ion battery is charged to 3.4V at 0.33C, and then placed at -20°C. After the battery body temperature drops to -20°C, it is discharged to 2.0V at 0.33C, and the discharge capacity is recorded as C0. Cycling is performed according to the above-mentioned charge and discharge mechanism, and the discharge capacity is recorded as C1 after 100 cycles. The low-temperature cycle capacity retention rate (%) = C1 / C0×100%.
[0187] The test results are shown in Table 3.
[0188] Table 3
[0189]
[0190]
[0191] From Table 3, we can see that:
[0192] Compared with Comparative Examples 1 to 8, the batteries in Examples 1 to 8 have higher gram capacity, electronic conductivity and sodium ion mobility, as well as higher energy density and low-temperature cycle capacity retention rate, wherein the low-temperature cycle capacity retention rate of Example 5 can reach up to 90.1%, which is significantly higher than that of Comparative Examples 1 to 8. It can be seen that the positive electrode active material in the present invention can significantly improve the energy density and low-temperature cycle performance of the battery.
[0193] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material includes a core and a carbon coating layer disposed on at least a portion of the surface of the core, wherein the core includes a chemical composition shown in Formula 1, NaFe x (PO4)2(P2O7) formula 1 In formula 1, 2.8≤x≤3.0; In the X-ray diffraction pattern of the positive electrode active material, there is a first diffraction peak at 2θ of 33.6°, and a second diffraction peak at 2θ of 32.9°, and the ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is greater than 22.
5.
2. The positive electrode active material according to claim 1, characterized in that The mass percentage C of the carbon coating layer in the positive electrode active material is 1.50wt%-2.15wt%; and / or, the median particle size D50 of the positive electrode active material is 8 μm-10 μm, and the specific surface area BET of the positive electrode active material is not higher than 13.5 m 2 / g.
3. The positive electrode active material according to claim 2, characterized in that The positive electrode active material satisfies any one of Formula 2, Formula 3, and Formula 4, 1.5%<C<1.7% and 8.5<BET<10.5 Formula 2; 1.7%≤C<1.9% and 10.5≤BET<11.5 Formula 3; 1.9%≤C<2.15% and 11.5≤BET<13.5 Formula 4.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The powder compaction density of the positive electrode active material is 1.91-2.01 g / cm 3 .
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The positive electrode active material also includes a doping element; The doping element includes at least one of B, F, Al, and N.
6. The positive electrode active material according to claim 5, characterized in that The mass percentage of the doping element in the positive electrode active material is 500ppm-2000ppm.
7. A method for preparing a positive electrode active material according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) mixing raw materials including a sodium source, an iron source, a phosphorus source, and a carbon source with deionized water to obtain a mixture; grinding the mixture to obtain a grind; the grind has a D10 of 0.10 μm-2 μm, a D50 of 0.25 μm-0.3 μm, and a D90 of 0.7 μm-1.0 μm; 2) spray drying the ground material to obtain a spray material; the spray material has a water content of ≤3% and a bulk density of ≤0.8 g / cm 3 ; 3) subjecting the spray material to fluidized drying treatment, during which: the fluidization temperature is 600° C.-1000° C., the gas flow rate is 5-20 m / s, and the fluidization time is 3-5 s to obtain a fluidized material; 4) Under a protective atmosphere, using a rotary kiln, sequentially performing a first sintering and a second sintering on the fluidized material to obtain the positive electrode active material; The temperature of the first sintering is 200-250° C., and the holding time is 1-2 hours; the temperature of the second sintering is 400-550° C., and the holding time is 10-20 hours.
8. The method for preparing a positive electrode active material according to claim 7, characterized in that: In step 1), grinding is performed by ball milling; The grinding comprises: performing first grinding and second grinding on the mixed material in sequence to obtain the grinding material; the first grinding has a rotation speed of 1000-1300 r / min, a grinding time of 30-50 min, and a particle size of the grinding beads of 0.6-0.8 μm; the second grinding has a rotation speed of 1400-1600 r / min, a grinding time of 30-60 min, and a particle size of the grinding beads of 0.3-0.4 μm; And / or, in step 2), the inlet air temperature during the spray drying process is 175-205°C, the outlet air temperature is 80-110°C, and the difference between the inlet air temperature and the outlet air temperature is 95-105°C.
9. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 6, or the positive electrode active material prepared by the preparation method according to claim 7 or 8.
10. A sodium ion battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 6, or the positive electrode active material prepared by the preparation method according to claim 7 or 8, or the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Polyanion positive electrode material as well as preparation method and application thereof
CN111446429A
Polyanionic sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
CN118213494A
Positive electrode material, preparation method thereof and sodium ion battery
CN118231652A
Positive electrode active material and sodium ion battery
CN118248869A
Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric device
CN118412453A
Cited By
Positive electrode active material, and preparation method therefor and use thereof
WO2026066466A1
